Protective sport bracing for athletes with mid-season shoulder instability - Baker, H. P.; Krishnan, P.; Meghani, O.; Athiviraham, A.; Ho, S.; Owens, B. D. (Sports Health: A Multidisciplinary Approach, 2023)
Context: In-season glenohumeral instability is a common clinical dilemma faced by physicians who care for athletes. Both nonoperative and operative management of athletes with in-season glenohumeral instability have been well described. Functional bracing remains less understood as a treatment modality. This review aims to provide an update on the most recent literature regarding the use of functional bracing for shoulder instability.